Tumor Suppressor miR-34a: Potential Biomarker of TACE Response in HCC - Zavadil, Jan; Juracek, Jaroslav; Cechova, Barbora; Rohan, Tomas; Husty, Jakub; Slaby, Ondrej; Litschmannova, Martina; Uher, Michal; Goldberg, S Nahum; Andrasina, Tomas (Cardiovascular and interventional radiology, 2025)
PURPOSE: TACE induces variable systemic effects by producing factors that promote inflammation, oncogenesis, and angiogenesis. Here we compare concentrations of microRNAs (miR-21, miR-210 and miR-34a) and vascular endothelial growth factor (VEGF) in hepatocellular carcinoma (HCC) patients undergoing TACE with degradable (DSM) and nondegradable (DEB) particles and potential use of these biomarker changes for prediction of patient outcomes. MATERIALS AND METHODS: Overall, 52 patients with HCC treated with DSM TACE (24 patients) and DEB TACE (28 patients) were included in this prospective study. Concentrations of studied biomarkers were measured from blood plasma preprocedurally, immediately (< 90 min) postprocedurally, and 24-h after TACE. Levels were compared between DSM and DEB TACE and correlated with treatment response six and 12 months after the first TACE. RESULTS: Both DSM and DEB TACE elevated plasma levels of miR-21, miR-34a, and miR-210 at 24 h post-procedure compared to baseline levels (FC 1.25-4.0). MiR-34a elevation immediately after TACE was significantly associated with nonprogressive disease compared to those with progressive disease at both six months (FCa: p = 0.014) and 12 months (FCa: p = 0.029) post-TACE. No significant biomarker changes were found between the embolization particle groups. However, VEGF levels showed a decrease only in the DSM TACE group (FC24: p = < 0.001). CONCLUSION: Embolization particle type did not significantly impact miRNA or VEGF changes post-TACE. However, miR-34a elevation immediately after the procedure predicts better patient outcome and may prove useful as a biomarkers for the monitoring of clinical outcomes. LEVEL OF EVIDENCE: Level 3 Prospective cohort study.
Keywords: Female; Hypoxia; Hepatocellular carcinoma; biologické markery; MicroRNA and vascular endothelial growth factor; hepatocelulární karcinom; Biomarkers; výsledek terapie; ženské pohlaví; vaskulární endoteliální růstový faktor A; lidé; Transarterial chemoembolization; nádory jater; Carcinoma, Hepatocellular; Vascular Endothelial Growth Factor A; Treatment Outcome; Tumor suppressor; chemoembolizace; Liver Neoplasms; prospektivní studie; Male; nádorové biomarkery; Prospective Studies; Aged; mikro RNA; MicroRNAs; lidé středního věku; Biomarkers, Tumor; senioři; mužské pohlaví; Middle Aged; Degradable and nondegradable particles; Chemoembolization, Therapeutic; Humans